Preparation and Characterization of Electrospun PLCL/Poloxamer Nanofibers and Dextran/Gelatin Hydrogels for Skin Tissue Engineering - Pan, Jian-feng (PLoS One, 2014)
In this study, two different biomaterials were fabricated and their potential use as a bilayer scaffold for skin tissue engineering applications was assessed. The upper layer biomaterial was a Poly(ε-caprolactone-co-lactide)/Poloxamer (PLCL/Poloxamer) nanofiber membrane fabricated using electrospinning technology. The PLCL/Poloxamer nanofibers (PLCL/Poloxamer, 9/1) exhibited strong mechanical properties (stress/strain values of 9.37±0.38 MPa/187.43±10.66%) and good biocompatibility to support adipose-derived stem cells proliferation. The lower layer biomaterial was a hydrogel composed of 10% dextran and 20% gelatin without the addition of a chemical crosslinking agent. The 5/5 dextran/gelatin hydrogel displayed high swelling property, good compressive strength, capacity to present more than 3 weeks and was able to support cells proliferation. A bilayer scaffold was fabricated using these two materials by underlaying the nanofibers and casting hydrogel to mimic the structure and biological function of native skin tissue. The upper layer membrane provided mechanical support in the scaffold and the lower layer hydrogel provided adequate space to allow cells to proliferate and generate extracellular matrix. The biocompatibility of bilayer scaffold was preliminarily investigated to assess the potential cytotoxicity. The results show that cell viability had not been affected when cocultured with bilayer scaffold. As a consequence, the bilayer scaffold composed of PLCL/Poloxamer nanofibers and dextran/gelatin hydrogels is biocompatible and possesses its potentially high application prospect in the field of skin tissue engineering.